The Role of English-language Community Organizations in Quebec's Immigration System - Shoumarova, Lina; Belkhodja, Chedly (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
English-speaking communities of Quebec (ESCQ) have a long history of welcoming immigrants and helping them settle in the province. For newcomers who don’t yet speak French, English-language organizations that offer integration and settlement services can act as a social entry point or “bridge” to Quebec society. They guide newcomers to essential services and French courses, and help them find jobs and housing and build social networks. This support eases the strains of migration and helps the vitality of English speaking communities, but also aligns with Quebec’s efforts to protect French and promote integration.

Presentation to the Standing Committee on Official Languages on Immigration as a Development Tool in Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2010)

Immigration : A perspective from Quebec's English-speaking communities : Prepared for the special National Assembly Committee on Immigration - Quebec Community Groups Network (QCGN) (2007)

Brief on the Green Paper of Immigration to the Special Joint Committee on Immigration Policy by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1975)
Any new Immigration Act ought to satisfy criteria which will make its spirit easily grasped by all people interested in the subject: it ought to be concise; it ought to spell out clearly a set of positive and basic principles governing regulations which will be issued from time to time to implement the Act - it being recognized that while the regulations themselves must be revised from time to time to make the Act applicable to changing circumstances, yet these must at all time represent in practice the spirit of the Act. Thus we agree with what the Green Paper indicated (Highlights Vol. 1 p. 18).